Macronuclei and micronuclei in Tetrahymena thermophila contain high-mobility-group-like chromosomal proteins containing a highly conserved eleven-amino-acid putative DNA-binding sequence. - Schulman, I G (1991)
HMG (high-mobility-group protein) B and HMG C are abundant nonhistone chromosomal proteins isolated from Tetrahymena thermophila macronuclei with solubilities, molecular weights, and amino acid compositions like those of vertebrate HMG proteins. Genomic clones encoding each of these proteins have been sequenced. Both are single-copy genes that encode single polyadenylated messages whose amounts are 10 to 15 times greater in growing cells than in starved, nongrowing cells. The derived amino acid sequences of HMG B and HMG C contain a highly conserved sequence, the HMG 1 box, found in vertebrate HMGs 1 and 2, and we speculate that this sequence may represent a novel, previously unrecognized DNA-binding motif in this class of chromosomal proteins. Like HMGs 1 and 2, HMGs B and C contain a high percentage of aromatic amino acids. However, the Tetrahymena HMGs are small, are associated with nucleosome core particles, and can be specifically extracted from macronuclei by elutive intercalation, properties associated with vertebrate HMGs 14 and 17, not HMGs 1 and 2. Thus, it appears that these Tetrahymena proteins have features in common with both of the major subgroups of higher eucaryotic HMG proteins. Surprisingly, a linker histone found exclusively in transcriptionally inactive micronuclei also has several HMG-like characteristics, including the ability to be specifically extracted from nuclei by elutive intercalation and the presence of the HMG 1 box. This finding suggests that at least in T. thermophila, proteins with HMG-like properties are not restricted to regions of transcriptionally active chromatin.